2012
DOI: 10.1007/s00464-012-2263-y
|View full text |Cite|
|
Sign up to set email alerts
|

Surgeons don’t know what they don’t know about the safe use of energy in surgery

Abstract: Many surgeons have knowledge gaps in the safe use of widely used energy-based devices. A formal curriculum in this area can address this gap and contribute to increased safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 6 publications
3
70
0
Order By: Relevance
“…These SAGES leaders did not know how to correctly handle a fire on the patient (31%), could not identify the electrosurgical device least likely to interfere with a pacemaker (31%), did not know that thermal injury could extend beyond the jaws of a bipolar instrument (13%), and thought a dispersive electrode should be cut to fit a child (10%). 33,34 Results among course participants and surgical trainees were similar to each other. 33,34 This finding demonstrated that surgical "experts" do not necessarily have greater knowledge of energy-based surgical devices compared with nonexpert surgeons or even junior trainees.…”
Section: Needs Assessmentmentioning
confidence: 55%
See 1 more Smart Citation
“…These SAGES leaders did not know how to correctly handle a fire on the patient (31%), could not identify the electrosurgical device least likely to interfere with a pacemaker (31%), did not know that thermal injury could extend beyond the jaws of a bipolar instrument (13%), and thought a dispersive electrode should be cut to fit a child (10%). 33,34 Results among course participants and surgical trainees were similar to each other. 33,34 This finding demonstrated that surgical "experts" do not necessarily have greater knowledge of energy-based surgical devices compared with nonexpert surgeons or even junior trainees.…”
Section: Needs Assessmentmentioning
confidence: 55%
“…33,34 Results among course participants and surgical trainees were similar to each other. 33,34 This finding demonstrated that surgical "experts" do not necessarily have greater knowledge of energy-based surgical devices compared with nonexpert surgeons or even junior trainees. These results highlight the need to educate trainees and surgeons in the knowledge and understanding of safe and appropriate use of energy-based surgical devices.…”
Section: Needs Assessmentmentioning
confidence: 55%
“…Since many surgeons are not aware of the tissue handling characteristics and limitations of new or reengineered devices, the knowledge gap can impact the clinical outcome of operations (Feldman, Fuchshuber et al 2012, Feldman, Brunt et al 2013, Sankaranarayanan, Resapu et al 2013, Chekan and Whelan 2014. Adverse events have been shown to be attributed to both user error as well as device-related errors.…”
Section: Clinical Knowledge Gapmentioning
confidence: 99%
“…Rapid technological advancement has allowed the development of highly complex, intricate medical devices, which is especially notable in the evolution of devices used for minimally invasive surgery (MIS) (Janetschek, Bagheri et al 2003, Feldman, Fuchshuber et al 2012, Chekan and Whelan 2014. MIS has become more applicable to an increasing number and variety of procedures and in many cases has become the preferred technique over open procedures (Belli, Fantini et al 2006, Hu, Gu et al 2009, Zingg, McQuinn et al 2009, Biere, van Berge Henegouwen et al 2012, Swanson, Meyers et al 2012.…”
mentioning
confidence: 99%
See 1 more Smart Citation